قياس كفاءة الورصات العربية عند المستوى الضعيف خلال الفترة 2017-2007 (Journal of Economic Additions, 2019)
The volatility in stock exchanges are one of the most debated issues in modernfinancial and economic literature, especially after the openness and financialintegration of the global economy and the recurrence of financial crises. This studyaims to measurement Efficient of Arab stock exchanges at the weak leve, Thestudy included four Arab stock exchanges: Saudi Arabia, Abu Dhabi, Qatar andAlgeria during the period 01-01-2007 to 31-12-2017, using daily data for stockindices, We apply Stationarity and Independence models. The study concludes thatthe returns of Arab stock exchanges Do not follow normal distribution and do notRandom walk, This means that the Arab stock markets are inefficient at the weaklevel.Keywords: Capital market efficiency, Random walk, Fat taille, Martingale model,Arab stock exchanges.Jel Classification Codes: C5, G15, E30 , M20